Analysis of Lexical Collocational Errors in Essays Committed by Double-majored Students at Hanoi National University of Education - Nguyen Thi Thanh Huyen, (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
This study is to classify main types of lexical collocational errors and identifying the possible causes of those errors in 63 essays by third-year double-majored students at Hanoi National University of Education (HNUE) based on the taxonomy proposed by Benson et al. (1997) and Richards (1973). It was found that Type 1 (verb + noun) in lexical collocational errors occurred most frequently in the participants’ writings and the lexical collocational errors were mainly due to the interlingual interference of Vietnamese. Some pedagogical implications are presented to alleviate those errors.Received 11th September 2019; Revised 18th April 2020; Accepted 24th April 2020